Civil-military 'legal' relations: where to from here? : the civilian courts and the military in the United Kingdom, United States and Australia - Collins, Pauline Therese (International humanitarian law series, 2018)
Civil-military relations establishes the civilian control over the military to protect democratic values. This book argues analysis of the CMR is distorted by the absence of consideration of the judicial arm, with the 'civil' seen as referring only to the executive and/or legislature. The civil courts approach to military discipline and the impact that has for CMR within - the United Kingdom, United States and Australia is investigated. The author concludes that by including the courts in the development of CMR theory militarisation of the civilian domain is discouraged. A paradigm shift acknowledging the fundamental role of all three organs of government in liberal democracies, for control of States' power is essential for genuine civilian oversight.